Reforming the Deprivation of Liberty Safeguards (DOLS): what is it exactly that we want? - Bartlett, Peter (University of Newcastle upon Tyne, 2014)
The Deprivation of Liberty Safeguards (DOLS) are the rules by which people who lack mental capacity can be deprived of liberty, most commonly in care homes or hospitals but also in supported accommodation and in the community more broadly. The present DOLS are not viewed as a success, and the Law Commission has a mandate reconsider a the legal framework for them. This paper is to start a debate as to what those revisions might look like.